Mapping of Epitopes on Human Tissue-Type Plasminogen Activator with Recombinant Deletion Mutant Proteins - Zonneveld, Anton-Jan van; Veerman, Harry; Brakenhoff, Just P J; Aarden, Lucien A; Cajot, Jean-Francois; Pannekoek, Hans (Thrombosis and Haemostasis, 1987)
An antigen assay based on a monoclonal antibody directed against the light chain of tissue-type plasminogen activator (t-PA) was developed to quantify seven recombinant (r) t-PA deletion mutant proteins. These recombinant proteins were then employed to map different epitopes on t-PA which interact with a panel of twenty-three monoclonal anti-t-PA antibodies. Twenty were directed against domains on the heavy chain, two against the “finger” domain, three against the “epidermal growth factor-like” domain, five against the kringle 1 domain, and ten against the kringle 2 domain. Only three monoclonal anti-t-PA antibodies interact with the light chain. The finding that the epitopes of each of the monoclonals could be determined with the deletion mutant proteins supports the hypothesis of autonomous folding of structural domains and emphasizes the validity of the use of the recombinant t-PA-deletion mutant proteins for structure-function studies.
Keywords: Recombinant tissue-type plasminogen activator; Monoclonal antibodies; Epitopes; Domain structure